Open-source lab how to build your own hardware and reduce research costs - Pearce, Joshua (Amsterdam Elsevier, 2014)
Open-Source Lab: How to Build Your Own Hardware and Reduce Scientific Research Costs details the development of the free and open-source hardware revolution. The combination of open-source 3D printing and microcontrollers running on free software enables scientists, engineers, and lab personnel in every discipline to develop powerful research tools at unprecedented low costs.--Provided by publisher.
Introduction to open-source hardware for science -- The benefits of sharing - nice guys and girls do finish first -- Open licensing - advanced sharing -- Open-source microcontrollers for science : how to use, design automated equipment with and troubleshoot -- RepRap for science? How to use, design, and troubleshoot the self-replicating 3-D printer -- Digital designs and scientific hardware -- The future of open-source hardware and science.
Includes bibliographical references and index.
Electronic reproduction.
Keywords: Laboratories -- Equipment and supplies; Open source software; Electronic books